Health and Counseling Service of Reproductive Health “I am Empowered Over my Body” - Suhaid, Dewi Novitasari; Aningsih, Baharika Suci Dwi; Dini, Kusuma; Kadarsih, Mitra; Purbo, Yoshepine Beni (AMK : Abdi Masyarakat UIKA, 2024)
Reproductive health is a crucial aspect of improving the quality of life, especially for women of reproductive age. However, knowledge about reproductive health, including early detection of breast and cervical cancer, remains low in many communities. Limited access to reproductive health services, particularly in remote and economically disadvantaged areas, exacerbates this issue. This community service program aimed to enhance public awareness and provide direct health services through the Reproductive Health Service and Counseling under the theme "I Am Empowered Over My Body." This initiative included essential health screenings such as blood pressure measurement, BMI calculation, cholesterol, uric acid, and glucose level tests, along with reproductive health counseling and early detection services for breast and cervical cancer through SADARI (Breast Self-Examination) and IVA (Visual Inspection with Acetic Acid) tests. The program was conducted on September 29, 2024, at STIK Sint Carolus Graduate Building, Jakarta, in collaboration with Ipas Indonesia, Jakarta Feminist, and Doctors Without Stigma. A total of 81 participants attended, with 38 undergoing basic health screenings, 9 receiving reproductive health counseling, and 34 participating in SADARI and IVA test. The results showed that 97.05% of IVA screening participants had normal results, while 2.74% tested positive and were referred for further examination. Awareness of breast cancer detection through SADARI was significantly improved, and all participants could repeat the procedure independently. Additionally, among participants in basic health screenings, 11.53% were identified with mild hypertension, 40.54% had high uric acid levels, and 77.78% had glucose levels exceeding the normal range, indicating a need for continuous health monitoring and intervention. This program successfully enhanced participants’ knowledge of reproductive health and increased access to essential screening services. Future initiatives should focus on sustaining these efforts through continuous education, destigmatization of reproductive health examinations, and strengthening community-based healthcare support.